Non‐invasive biological quantification of acute gastrointestinal graft‐versus‐host disease in children by plasma citrulline. (1st August 2013) - Merlin, E.; Minet‐Quinard, R.; Pereira, B.; Rochette, E.; Auvrignon, A.; Oudot, C.; Sapin, V.; Deméocq, F.; Kanold, J.
Abstract Clinical grading of GI involvement during acute GVHD remains a challenging issue, especially in children. Plasma citrulline, a non‐protein amino acid selectively produced and released by enterocytes, is a suitable surrogate endpoint for small intestinal epithelial cell mass, irrespective of the underlying cause of cell loss. Children referred for allogeneic bone marrow transplantation who were free from chronic malabsorption or constitutional disease involving the GI tract were consecutively included in this prospective study. Plasma citrulline and albumin concentration was measured every week between day 7 and day 28 of BMT until resolution of the aGVHD or occurrence of chronic GVHD. In total, 31 children were included between 2008 and 2011. After a CR, citrulline levels fell to a minimum level on day 7 and then increased to reach the initial value on day 28. After day 28, plasma citrulline but not albumin was strongly linked to the occurrence of GI GVHD, the threshold being set at 10 μmol/L. The correlation with clinical grade of GI‐aGVHD now needs to be assessed in larger populations. In pediatric patients, citrulline is valuable as a suitable non‐invasive marker of GI involvement in acute GVHD.